2012
DOI: 10.1177/0013916512452428
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Long-Term Impacts of Climate Change Communications on Individuals’ Attitudes and Behavior

Abstract: To assess the effectiveness of climate change communications, it is important to examine their long-term impacts on individuals' attitudes and behavior. This article offers an example study and a discussion of the challenges of conducting long-term investigations of behavioral change related to climate change communications (a vital and under-researched area). The research reported is a longitudinal panel study of the impacts on UK viewers of the climate change movie The Age of Stupid. The heightened levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 75 publications
(97 reference statements)
5
60
0
5
Order By: Relevance
“…Research shows that information can make a difference in some circumstances, but it is often insufficient to elicit desired behaviors (Schultz, 2002). Two recent articles (Howell, 2014;Nolan, 2010), for example, examine the knowledge-deficit framework by studying the effects of attending movies intended to heighten concern about climate change. Howell found that while receiving information through the film media increased concern about the issues, those effects on attitudes were not long-lasting.…”
Section: The Deficit Modelmentioning
confidence: 99%
“…Research shows that information can make a difference in some circumstances, but it is often insufficient to elicit desired behaviors (Schultz, 2002). Two recent articles (Howell, 2014;Nolan, 2010), for example, examine the knowledge-deficit framework by studying the effects of attending movies intended to heighten concern about climate change. Howell found that while receiving information through the film media increased concern about the issues, those effects on attitudes were not long-lasting.…”
Section: The Deficit Modelmentioning
confidence: 99%
“…Barr, 2003;Lorenzoni et al, 2007). Howell (2014) suggests that such campaigns e especially if they focus on big, complex problems -can invoke lethargy, i.e., cause a feeling of disempowerment. Similarly, Kaplan (2000) states that people tend to avoid information campaigns that result in them feeling helpless or apathetical.…”
Section: The Engagement Phasementioning
confidence: 99%
“…By communicating with peers, the individual realises he is not alone in considering or making changes (Heiskanen et al, 2010). This realisation may overcome feelings of lethargy (Howell, 2014). Interventions that stimulate social interaction can make use of these psychological phenomena, as is proposed by for example by Gardner and Stern (1996) and Heiskanen et al (2010).…”
Section: The Engagement Phasementioning
confidence: 99%
“…Focusing on more long-term impacts, however, may give a different picture. The longitudinal panel study, which examined the impacts on UK viewers of a climate change movie, "The Age of Stupid" (Howell 2014), showed that the heightened levels of concern and sense of urgency to act initially generated by the movie did not measurably persist over the long term.…”
Section: Informationmentioning
confidence: 99%